2011
DOI: 10.1063/1.3534026
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities and transition in flows between two porous concentric cylinders with radial flow and a radial temperature gradient

Abstract: Complex regimes arising after the loss of stability of a viscous fluid with radial flow and radial temperature gradient between two heated rotating permeable cylinders are investigated in a small neighborhood of the point of intersection of neutral curves of monotonic axisymmetric and oscillatory three-dimensional instabilities. Since by the linear theory we can form a judgment only of the first loss of instability, the development of complex flows is investigated by nonlinear analysis, which makes it possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The algorithm for calculating the coefficients of the amplitude system is described in [12] and is similar to the algorithm used in studies of the isothermal [4] and non-isothermal [13,14] Couette flow between cylinders.…”
Section: Calculation Of the Coefficients Of The Amplitude Systemmentioning
confidence: 99%
“…The algorithm for calculating the coefficients of the amplitude system is described in [12] and is similar to the algorithm used in studies of the isothermal [4] and non-isothermal [13,14] Couette flow between cylinders.…”
Section: Calculation Of the Coefficients Of The Amplitude Systemmentioning
confidence: 99%
“…The calculations for impermeable [9] and permeable heated [16] cylinders showed that the J-bound pairs of nonsymmetric cycles of the motor subsystem undergo bifurcation of period doubling, including unbounded sequences of these bifurcations. Analogous phenomena take place in the case under consideration.…”
Section: Calculation Of the Cycles Of The Motor Subsystemmentioning
confidence: 99%
“…Cylindrical vortices with radial flow were already studied in Refs. [23,25,26,[30][31][32][33][34][35][36][37], but the problem of finding cooling scenarios with proper boundary conditions was (to our knowledge) not posed. Dornbrand [25] and later on Pengelley [26] studied the problem precisely having the same purpose as we: to get a solvable model for vortex cooling.…”
mentioning
confidence: 97%
“…Refs. [31,33,35,36] focus on a laminar flow in the incompressible limit (but they account for axial motion). As our analysis shows, compressibility does not need to be large, but retaining it-and hence allowing for the proper coupling between thermodynamics and mechanics-is necessary for the proper theoretical description of cooling.…”
mentioning
confidence: 99%